The social support network of teenage mothers in Botshabelo - Motjelebe, Nthabiseng Joyce (Stellenbosch : University of Stellenbosch, 2009)
A qualitative and quantitative approach was chosen together with an exploratory and descriptive design in order to obtain knowledge, insight and understanding regarding the utilization of social support network of teenage mothers in Botshabelo. It is necessary for social workers to identify the social support systems that exist in a social support network of teenage mothers in order to select those systems which would be relevant to meet the needs of teenage mothers. The aim of this study is to present guidelines for social workers to empower teenage mothers to utilize social support networks to fulfil their roles as parents. A sample of ten teenage mothers (14 years to 19 years of age) who are from the service area at the J clinic in Botshabelo was involved in the study. A qualitative investigation was carried out by means of conducting interviews with the aid of a semi-structured interview guide. The responses of the participants and the findings of the study were analyzed and compared with the findings of previous studies. The results of the investigation confirmed that the findings of the literature study namely that teenage parenting severely impacts daily functioning of teenage mothers. These challenges include aspects related to financial problems, responding to the baby’s needs, attending classes or seeking for a job, while expected to play a mother’s role at the same time. The results of the study gave an indication of the nature of social work intervention that is needed for this target group: talking to someone, distributing information regarding teenage parenting, distributing information regarding available services, participating in a support group and learning to cope with daily activities. The findings of the research can be used as guidelines by social workers who need to empower teenage mothers to utilize their social support network.